Differences in the bacteriome of swab, saliva, and tissue biopsies in oral cancer - Gopinath, Divya; Menon, Rohit Kunnath; Wie, Chong Chun; Banerjee, Moinak; Panda, Swagatika; Mandal, Deviprasad; Behera, Paresh Kumar; Roychoudhury, Susanta; Kheur, Supriya; Botelho, Michael George; Johnson, Newell W. (Scientific reports, 2021)
Microbial dysbiosis has been implicated in the pathogenesis of oral cancer. We analyzed the compositional and metabolic profile of the bacteriome in three specific niches in oral cancer patients along with controls using 16SrRNA sequencing (Illumina Miseq) and DADA2 software. We found major differences between patients and control subjects. Bacterial communities associated with the tumor surface and deep paired tumor tissue differed significantly. Tumor surfaces carried elevated abundances of taxa belonging to genera Porphyromonas, Enterobacteriae, Neisseria, Streptococcus and Fusobacteria, whereas Prevotella, Treponema, Sphingomonas, Meiothermus and Mycoplasma genera were significantly more abundant in deep tissue. The most abundant microbial metabolic pathways were those related to fatty-acid biosynthesis, carbon metabolism and amino-acid metabolism on the tumor surface: carbohydrate metabolism and organic polymer degradation were elevated in tumor tissues. The bacteriome of saliva from patients with oral cancer differed significantly from paired tumor tissue in terms of community structure, however remained similar at taxonomic and metabolic levels except for elevated abundances of Streptococcus, Lactobacillus and Bacteroides, and acetoin-biosynthesis, respectively. These shifts to a pro-inflammatory profile are consistent with other studies suggesting oncogenic properties. Importantly, selection of the principal source of microbial DNA is key to ensure reliable, reproducible and comparable results in microbiome studies.